Implementation of the Topsis Method in Determining Online Shopping Options in the Marketplace - Tuslaela, Tuslaela; Alawiah, Enok Tuti; Apriyani, Helina (Institute of Computer Science (IOCS), 2025)
The development of information technology changes the way customers view shopping. Currently, customers are more likely to make online shopping transactions through the marketplace. Significantly increased internet penetration, ease of transactions, seller reputation, speed of service, ease of access are factors that support customers in making shopping transactions in the marketplace. However, customers need to decide wisely before making a shopping transaction so that the products obtained are in accordance with expectations. This study uses the TOPSIS method, a method in the decision-making process to choose an ideal solution based on the criteria offered. The results of the study obtained a result of 0.85 for product reviews as an alternative preference in shopping online through the marketplace.